Enhancing Inventory and Transaction Management with Integrated E-Commerce Solutions: A Case Study of Desasa Home Decor - Utami, Yohana Tri; Faradila, Dita; Ramadhanti, Karina Adityas; Muhaqiqin; Taufik, Rahman (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
Esasa Home Decor is a store that specializes in selling various types of artificial flower home decorations. The use of information technology in data management is essential to ensure that inventory and transaction management are conducted swiftly and generate accurate reports. This system is integrated with the Shopee API to automatically retrieve product and transaction data. This integration allows for better monitoring of stock levels and transactions on the e-commerce platform, ensuring that the information remains up-to-date. The development method used in this study is Extreme Programming, which emphasizes close collaboration within the team and continuous testing to produce high-quality software. Data collection was conducted through interviews, analysis, and direct observation of the ongoing business processes at Esasa Home Decor. The result of this research is a management information system that facilitates store management and is integrated with the Shopee e-commerce platform. The User Acceptance Testing (UAT) yielded a score of 97.714%, indicating that the system is highly suitable for use. Additionally, the Black-Box testing concluded that the system functions as expected and according to plan. Thus, this system enhances the operational efficiency of Esasa Home Decor by streamlining inventory and transaction management while providing more accurate and timely reports.